The use of Moringa oleifera in ruminant feeding and its contribution to climate change mitigation - Amad, Abdulkarim Abdulmageed; Zentek, Jürgen (Frontiers in Animal Science, 2023)
Livestock production in developing countries faces several difficulties such as a general shortage of feed resources, regional availability, and quality. Climate change further exacerbates these problems, leading to a massive reduction in ruminant productivity. Therefore, there is a need for the use of adaptable and resilient forage plants that can also contribute to reducing greenhouse gases. The Moringa oleifera tree is well known as an agroforestry tree and has adapted to growing in harsh conditions. It produces a high amount of biomass in a short period and contains high levels of nutrients and biologically active components. All parts of the Moringa tree are valuable and have multiple benefits and applications. Therefore, Moringa oleifera has great potential and can be used as a forage crop, storing carbon dioxide (CO2) and improving ruminant performance and the livelihoods of farmers in the tropics. This article aimed to present the results and findings of studies related to the use of Moringa in ruminant feed (cattle, sheep, and goats) and its contribution to climate protection. Several studies highlighted that M. oleifera can be used as green fodder either individually or in combination with other crops or concentrate feeds to improve the performance of ruminants, such as the growth rate, milk yield, and milk constituents, without negatively impacting animal health. This improvement in performance could be attributed to the favorable nutrient content in M. oleifera, delivering proteins in conjunction with bioactive compounds such as alkaloids, flavonoids, phenolics, glucosinolates, carotenoids, sterols, saponins, phenolic acids, tannins, and isothiocyanates. Furthermore, it has been shown that this plant can be produced in high yields and thus might be an excellent carbon dioxide sink to absorb and utilize carbon dioxide, reducing the anthropogenic load of carbon dioxide in the atmosphere. In addition, feeding cattle and other ruminants with M. oleifera leaves or seeds significantly decreases ruminal methane emissions, which could contribute to adapting to climate-friendly farming. Thus, the use of Moringa can make a sustainable contribution to strengthening animal production, especially in countries with limited feed resources.